THE EFFECT OF MASERATION TIME VARIATION ON THE FORMULATION OF DEODORANT SPRAY FROM BASIL LEAVES (Ocimum basilicum L.) - Usfa, Azra Arzahri; Suryani, S; Syafruddin, S (Politeknik Negeri Lhokseumawe, 2025)
This study evaluated the effect of maceration time variation on the characteristics of basil leaf extract (Ocimum basilicum L.) and the performance of deodorant spray preparations containing the extract. Maceration was carried out using 96% ethanol for 2, 3, 4, 5, and 6 days. The extract was then formulated into a deodorant spray at concentrations of 5–25% (v/v). The parameters observed included yield, pH, antibacterial activity against Staphylococcus epidermidis (colony count/CFU method), and organoleptic testing (color, aroma, and after feel) by 25 panelists. The yield increased with maceration time from 8.64% (day 2) to 10.82% (day 6). The pH value of the preparation was 4.9–5.2, in accordance with SNI 16-4951-1998 and close to the physiological pH of the skin. Commercial deodorants reduced the number of bacterial colonies by 50%, while basil extract deodorants reduced it by 20% in the test concentration range. Organoleptically, the 15% concentration was most preferred by the panelists. These findings indicate that basil extract has potential as an active ingredient in natural spray deodorants; optimization of concentration, formulation base, and further statistical testing are recommended to enhance antibacterial efficacy.Keywords: Deodorant Spray, basil leaves, Ocimum basilicum L., maceration, antibacterial, organoleptic.